CONCENTRATION OF ORANGE JUICE BY USING ROTARY VACUUM EVAPORATOR TO PROTECT FLAVOR COMPOUNDS - Khattab , Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This paper is an attempt to protect the main flavor compounds in concentrated orange juice by using vacuum evaporator technique, instead of the traditional method which causes a remarkable degradation in these compounds. The physiochemical and microbial properties of juice were monitored throughout the concentration processes. Rotary evaporator technique was used at different conditions to concentrate orange juice and comparing with traditionally heat treatment. Total soluble solid (TSS), ascorbic acid, acidity, pH, viscosity and tannins have been affected by various levels according to concentration technique and period of storage. The microbial content had never developed even throughout the storage for six months, because we have added 100 ppm sodium benzoate to the fresh juice immediately after squeezing. The main flavor compounds in fresh orange juice have been monitored throughout the various concentration processes to judged their abilities for maintaining the flavor compounds of concentrated juice.